Life history of common dolphins (Delphinus delphis) in Aotearoa New Zealand : a thesis submitted in partial fulfilment of the requirements for the degree of Doctor of Philosophy (PhD) in Zoology at Massey University, Albany, Aotearoa New Zealand - Palmer, Emily (Massey University, 2023)
Common dolphins (Delphinus delphis) are a globally distributed species and have been extensively studied in the Northern Hemisphere, predominantly through strandings and fisheries bycatch. Within Aotearoa New Zealand waters, there is a lack of understanding of the life history of common dolphins. In this study, critical parameters of age, growth and reproductive biology from 562 individuals (269 females, 270 males and 23 unsexed individuals) were assessed from stranding and bycatch events around the Aotearoa New Zealand coast. Age was estimated from decalcified thin sections of teeth. Males and females ranged in total body length from 89 to 244 cm and 82 to 233 cm, respectively. The maximum age recorded for males and females was 26 and 29 years, respectively. Physical maturity was determined when asymptotic length was obtained using Gompertz growth models. Males obtained physical maturity at 212.1 cm and 20 years of age and females obtained physical maturity at 198.3 cm and 18 years of age. Sexual size and shape dimorphism was observed for common dolphins, with males being significantly larger than females for 9 (size) and 8 (shape) out of 24 characters measured. Reproductive parameters were assessed in 104 females and 64 males via the gross and histological examination of the gonads. The average age and length at attainment at sexual maturity for males and females was 8.76 years and 198.4 cm, and 7.5 years and 183.5 cm, respectively. Reproductive seasonality was observed in males but not in females. A pregnancy rate of 30% and a calving interval of 3.2 years were determined with gestation, lactation, and resting periods lasting for 12.6–12.8 months, each. Length at birth was estimated at 85.4 cm. Parameters estimated in this study align with global populations though slight variation may indicate population-level differences. The Aotearoa New Zealand population of common dolphins is part of a greater Australasian population that experiences a wide range of anthropogenic impacts. Biological parameters estimated here can now be used as a baseline to monitor any future changes. This thesis has significant implications for the conservation and management of common dolphins in Aotearoa New Zealand waters.
Keywords: science, conservation biology, zoology, life history, reproduction; 310307 Population ecology